Variety of Adverse Reactions in Rats after Administration of Combination of Anti-tuberculosis and Antimicrobial Drugs with Different Safety Profiles - G. N. Mozhokina; Yu. R. Zyuzya; L. Yu. Petrova; A. G. Samoylova (Туберкулез и болезни лёгких)
The objective: to evaluate the variety of adverse reactions to combinations of clofazimine with anti-tuberculosis and antimicrobial drugs with different and similar toxic profiles.Subjects and Methods: Studies were carried on non-pedigree female rats at the age of 10-11 months. In Group 1, rats received Cfz + Bdq + Mxf + Clr, in Group 2 – Cfz + Bdq + Lzd + Z daily for 14 days. A comprehensive examination upon completion of drug administration included functional (ECG, behavioral reactions), laboratory and pathomorphological assessments.Results. The combination of Cfz + Bdq + Mxf + Clr had a pronounced cardiotoxicity: it caused QT prolongation up to 0.053 ± 0.002 s and individual fluctuations within ranges up to 20 ms; some rats demonstrated qualitative ECG changes. Hepatotoxic reactions were revealed according to laboratory and morphological parameters, and morphological signs of mild kidney dystrophy were found in most rats. Neurotoxic reactions were manifested as a decrease in motor and exploratory activities. The combination of Cfz + Bdq + Lzd + Z did not cause significant ECG changes; mild signs of hepatotoxicity and nephrotoxicity were observed in single rats, behavioral disorders manifested only as emotional depression of the animals. Significant differences in the variety and degree of adverse reactions are due to the combination of clofazimine with drugs possessing similar cardiotoxic potential – bedaquiline, moxifloxacin, and clarithromycin.